Understanding abscisic acid-mediated stress signaling to affect rice development under stress - Gul, Rao Muhammad Samran; Rauf, Saeed; Ortiz, Rodomiro; Waqas Khalid, Muhammad; Kaya, Yalcin (Frontiers in Sustainable Food Systems, 2024)
Rice is an important staple food of many nations and its yield is known to be affected by various abiotic stresses that will likely increase under climate change, thereby affecting global food security. On the other hand, abscisic acid (ABA) is a crucial plant growth regulator under various abiotic stress factors. It mediates several responses in plants such as seed dormancy, leaf gas exchange parameters, reactive oxygen species (ROS) scavengers, ion toxicity, and root length elongation; thus improving plant survival under stress.This article reviews recent research on ABA mediated gene response and expression involved in the rice plant architecture and under abiotic stress.The ABA responses occurred as result of altered gene expression.Expression analyses of the gene related to ABA biosynthesis or catabolism indicated several changes in the architecture such as leaf angle, delayed flowering, altered growth regulators and tolerance related mechanisms such as increased ROS, low membrane leakage, vacuolar compartmentation of toxic radicals under multiple or single stress factors. These responses may improve plant survival under stress, provide yield sustainability but may not increase yield potential in a stressful environment affected by drought salinity or heat stress. The expression of ABA was related to improvement of pollen viability, grain filling potential and seed setting under abiotic stress such as heat, which may be helpful in seed yield improvement.